2013
DOI: 10.1039/c3ee23917a
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the chemical expansion coefficient in ceria by addition of zirconia

Abstract: Chemical expansion, the lattice parameter increase upon change in the oxide stoichiometry, was decreased, for the fi rst time, by controlling lattice relaxations around a vacancy. Advanced experimental techniques (I2CNER and Tohoku University) combined with state-of-the-art Density Functional Theory (Trinity College Dublin) facilitated this achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…The fact that strained bonds reduces the ceria reduction energy corrects a long held misunderstanding that they compensate for ceria expansion. 33,[35][36][37][38] Additionally, this explanation provides the fundamental understanding for why the geometric relaxation of Zr-CeO 2 during reduction is associated with a decreased Ovacancy formation energy. 59 While the energy released is sizable, it does not decrease the reduction energy to the same extent as the presence of pre-broken bonds or decreased electron promotion energy.…”
Section: Straining O-bondsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fact that strained bonds reduces the ceria reduction energy corrects a long held misunderstanding that they compensate for ceria expansion. 33,[35][36][37][38] Additionally, this explanation provides the fundamental understanding for why the geometric relaxation of Zr-CeO 2 during reduction is associated with a decreased Ovacancy formation energy. 59 While the energy released is sizable, it does not decrease the reduction energy to the same extent as the presence of pre-broken bonds or decreased electron promotion energy.…”
Section: Straining O-bondsmentioning
confidence: 99%
“…33,[35][36][37][38] This nding builds on the work of Wang et al, who suggested that structural relaxation is the driver for the decreased reduction energy, 59 by explaining that the energy released during structural relaxation stems from strain release of the Zr-O bonds. The promotion of two electrons into the Ce forbitals and breakage of four O-cation bonds results in an Ovacancy formation energy that is high enough to drive water splitting when the vacancy is lled.…”
Section: Performance Improving Materials: Tetravalent Dopantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, to increase fracture strength and to avoid Figure 4a and e do not correspond to any previous samples cracking of GDC during co-firing in a reducing atmosphere, GDC20 should be sintered to result in low porosity and small grain size. Reduction of chemical-expansion coefficient by adding ZrO 2 in the CeO 2 is also a feasible way [15,43,44]. To avoid cracking, we suggest sintering GDC20 at T < 1088°C or at Po 2 >10 −15 atm or both, or sintering GDC20 to result in little porosity with small grain size.…”
Section: Resultsmentioning
confidence: 96%